Stepping toward implementation using co-design: development of hospital protocols and resources for using wearable activity trackers in a hospital service - Szeto, Kimberley; Davis, Aaron; Arnold, John; Gwilt, Ian; Forrest, Aislin; Heyne, Isaac; Hewitt, Anthony; Diestel-Feddersen, Peter; Edwards, Dominique; Singh, Ben; Maher, Carol (Frontiers in Digital Health, 2025)
IntroductionLow levels of patient physical activity during a hospital stay are linked to a variety of poor outcomes. Wearable activity trackers can help to boost patient activity and improve other outcomes during a hospitalisation, but a range of implementation barriers exist. Co-design research methodologies provide opportunities to bridge evidence-practice gaps, such as the implementation of wearable activity trackers to promote patient activity, by developing solutions and strategies in collaboration with key stakeholders. This co-design study aimed to develop a protocol and resources to support the implementation of wearable activity trackers into a rehabilitation service at a South Australian hospital.MethodsThree co-design workshops that employed an involvement partnership with 26 rehabilitation clinicians were conducted. User journey storyboards, empathy maps, and world café activities were used to understand processes of using technology with patients in the hospital, identify protocol components for using WATs, and create resources to support its implementation.ResultsUsing a co-design approach, this study developed a protocol for using WATs in a hospital rehabilitation services, identified key themes underpinning its implementation, and created a set of resources to support its delivery.DiscussionThis study identified key elements to support implementation of WATs in hospital rehabilitation, and expands the evidence base for using co-design approaches in health research, and may support WAT implementation in other settings.